Peran Sastra Arab dalam Dakwah Islam - Sutisna, Dede; Rohanda, Rohanda; Atha, Yusuf Ali Shaleh (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2024)
This research aims to analyze the role of Arabic literature in spreading Islamic da'wah, especially in conveying moral and spiritual messages to society. The method used is a literature study with a descriptive qualitative approach, by collecting data from various reference sources whose validity and scholarship can be accounted for relating to Arabic literature and Islamic preaching. Research findings show that Arabic literature has an important role in Islamic da'wah, because it is able to convey religious messages in a subtle and interesting way through symbols, metaphors and moral stories. Literary works such as poetry, prose and sagas are not only a means of entertainment but also an effective means of learning and spreading Islamic teachings. Arabic literature enriches people's understanding of Islamic values with an aesthetic and intellectual approach, so that it can attract the interest of various groups of readers. This research shows that the integration of Arabic literature in da'wah strategies can increase the appeal of Islamic messages, especially in the modern era, where creative and humanist approaches are becoming increasingly relevant.